Customer Satisfaction Perception in Application Use Mobile Banking JConnect Bank East Java in Surabaya City - Reyhan Ananda Ganda; Herwin Ardianto (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2026)
The development of information technology has encouraged banks to transform towards digital services, particularly through mobile banking applications. This study aims to examine customer satisfaction with the Bank Jatim JConnect Mobile application in Surabaya. This study uses a qualitative descriptive approach, including interviews, questionnaires, and observations of JConnect mobile banking customers. The research results show that most respondents were satisfied with the mobile banking platform Jconnect. The highest user satisfaction was in aspects of service quality (68%), feature relevance (62%), transaction security (55%), and ease of use (50%). Respondents also provided suggestions for feature development, such as adding real-time notifications, video tutorials, credit due reminders, and double security. The findings of this study are expected to provide input for application service providers, namely Bank Jatim, to improve the quality of digital services to meet customer needs and expectations, and to strengthen competitiveness in the digital banking era.